THE DEVELOPMENT OF INTEGRATED SCIENCE PRACTICE ON SKIN HEALTH THEME ‎TO ENHANCE THE SCIENCE PROCESS SKILL OF JUNIOR HIGH SCHOOL STUDENTS ‎ - Purnamasari, Shinta; Surtikanti, Hertien (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
Science learning have to able to provide direct experiences to the students, so they not only learn the concepts and theories, but also can learn science as a process through lab activity. In middle school, science learning conducted in integrated mode in order to provide opportunities for students to understand the phenomenon from various sides. The aim of this study was to produce an experiment procedure to teach integrated science in skin health theme that can be implement it in learning process. A hands-on activity is presented in worksheet form. This study used Research and Development method. The stages were conducted in this study consist of preliminary studies and model development. Data collected through experts assessment sheet, and readability questionnaire and science process skills test. Based on experts assessment sheet obtained that experiment procedure has a good quality with average percentage about 90.56% which includes didactic aspect (93.21%), construction aspect (88.89%), and technical aspect (91.67%). An experiment procedure was presented in worksheet form andhas a very good readability level with average percentage about 82.80%. The test result showed that an experiment procedure can enhance students’ science process skills especially in doing an experiment aspect. Keywords: experiment development; integrated science experiment; skin health; sunscreen.